SEARCHPKS: a program for detection and analysis of polyketide synthase domains - Yadav, Gitanjali (Oxford University Press, 2003)
SEARCHPKS is a software for detection and analysis of polyketide synthase (PKS) domains in a polypeptide sequence. Modular polyketide synthases are unusually large multi-enzymatic multi-domain megasynthases, which are involved in the biosynthesis of pharmaceutically important natural products using an assembly-line mechanism. This program facilitates easy identification of various PKS domains and modules from a given polypeptide sequence. In addition, it also predicts the specificity of the potential acyltransferase domains for various starter and extender precursor units. SEARCHPKS is a user-friendly tool for correlating polyketide chemical structures with the organization of domains and modules in the corresponding modular polyketide synthases. This program also allows the user to extensively analyze and assess the sequence homology of various polyketide synthase domains, thus providing guidelines for carrying out domain and module swapping experiments. SEARCHPKS can also aid in identification of polyketide products made by PKS clusters found in newly sequenced genomes. The computational approach used in SEARCHPKS is based on a comprehensive analysis of various characterized clusters of modular polyketide synthases compiled in PKSDB, a database of modular polyketide synthases. SEARCHPKS can be accessed at http://www.nii.res.in/searchpks.html.